Comparative evaluation of quetiapine plus lamotrigine combination versus quetiapine monotherapy (and folic acid versus placebo) in bipolar depression (CEQUEL): a 2 × 2 factorial randomised trial. (January 2016) - Geddes, John R; Gardiner, Alexandra; Rendell, Jennifer; Voysey, Merryn; Tunbridge, Elizabeth; Hinds, Christopher; Yu, Ly-Mee; Hainsworth, Jane; Attenburrow, Mary-Jane; Simon, Judit; Goodwin, Guy M; Harrison, Paul J; et al.
Summary: Background: Depressive symptoms are a major cause of disability in bipolar disorder and there are few safe and effective treatments. The combination of lamotrigine plus quetiapine potentially offers improved outcomes for people with bipolar depression. We aimed to determine if combination therapy with quetiapine plus lamotrigine leads to greater improvement in depressive symptoms over 12 weeks than quetiapine monotherapy plus lamotrigine placebo. Methods: In this double-blind, randomised, placebo-controlled, parallel group, 2 × 2 factorial trial (CEQUEL), patients with DSM-IV bipolar disorder I or II, who were aged 16 years or older, and required new treatment for a depressive episode, were enrolled from 27 sites in the UK. Patients were randomly assigned (1:1) by an adaptive minimisation algorithm to lamotrigine or placebo and to folic acid or placebo. Participants and investigators were masked to the treatment groups. The primary outcome was improvement in depressive symptoms at 12 weeks with the Quick Inventory of Depressive Symptomatology—self report version 16 (QIDS-SR16). Analysis was by modified intention-to-treat. This trial is registered with EUdraCT, number 2007-004513-33. Findings: Between Oct 21, 2008, and April 27, 2012, 202 participants were randomly assigned; 101 to lamotrigine and 101 to placebo. The mean difference in QIDS-SR16 total score between the group receiving lamotrigine versus the placebo group at 12 weeks was −1·73 ([95% CI −3·57 to 0·11]; p=0·066) and at 52 weeks was −2·69 ([–4·89 to −0·49]; p=0·017). Folic acid was not superior to placebo. There was a significant interaction (p=0·028), with folic acid reducing the effectiveness of lamotrigine at 12 weeks. The mean difference on QIDS-SR16 was −4·14 ([95% CI −6·90 to −1·37]; p=0·004) for patients receiving lamotrigine without folic acid compared with 0·12 ([–2·58 to 2·82]; p=0·931) for those receiving lamotrigine and folic acid. Interpretation: Addition of lamotrigine to quetiapine treatment improved outcomes. Folic acid seems to nullify the effect of lamotrigine. CEQUEL should encourage clinicians and patients to consider lamotrigine for bipolar depression, but also to be aware that concurrent folic acid might reduce its effectiveness. Funding: Medical Research Council.